PERENCANAAN KONSTRUKSI BANGUNAN ATAP LAPANGAN OLAHRAGA UNIVERSITAS BANGKA BELITUNG MENGGUNAKAN STRUKTUR BUSUR - Ray Makkawaru; Donny Fransiskus Manalu; Endang Setyawati Hisyam (Jurusan Teknik Sipil Universitas Bangka Belitung, 2018)
Wide span building is kind of building that need large space without any poles in the centre. Roof building construction is wide span structure that overshadow footsal, basketball and volley field in Bangka Belitung University. Arc structure become one of construction structures that often used in wide span buildings. In this planning, steel constructions using LRFD method. The result from this planning is dimention of gording using canal profil type 150.75.6.5.10 with quality of steel is BJ41. For trekstang/sargod using plain steel with diameter mm. Portal rafter using round profil PSB 10 inch diameter and coloumn using WF profil 458.417.30.50 with quality of steel is BJ41. Base plate dimentions is (600x600) mm with 32 mm thick for 16 bolts with inch diameter and 10 mm endplate for 6 high quality bolts type A490 with mm diameter. Dimentions of pedestal coloumn is (1400x1400) mm, 1400 mm high with 40 25-100 main reincforcement and 13-400 crossbar with fc’ 25 Mpa, fy 400 MPa. Dimentions of footplate pondations is (2100x2100)mm with 600 mm thick, pondations reinforcement using plain steel diameter and stek reinforcement using 16D29 with fc’=25 Mpa, fy=400 Mpa.